Google Earth and GIS reveal settlement patterns associated with stone circles, southern Gauteng, South Africa - Banhegyi, Stephen (My University, 2015)
Unable to load abstract.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science.
Keywords: Land settlement patterns - South Africa - Gauteng.; Geographic information systems.